2010
DOI: 10.1164/rccm.200908-1201oc
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Associations between Ambient Air Pollutants and Pediatric Asthma Emergency Department Visits

Abstract: Rationale: Certain outdoor air pollutants cause asthma exacerbations in children. To advance understanding of these relationships, further characterization of the dose-response and pollutant lag effects are needed, as are investigations of pollutant species beyond the commonly measured criteria pollutants. Objectives: Investigate short-term associations between ambient air pollutant concentrations and emergency department visits for pediatric asthma. Methods: Daily counts of emergency department visits for ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
231
1
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(258 citation statements)
references
References 49 publications
18
231
1
5
Order By: Relevance
“…The hypothesis that a positive temporal relationship exists between the daily number of first consultations for respiratory diseases and the daily concentration of PM 10 was thus certainly confirmed in the Zagorje and Trbovlje municipalities. Moreover, these results are consistent with the results of many similar studies (23,(48)(49)(50) that also confirmed the positive association between respiratory diseases and PM 10 concentration.…”
Section: Discussionsupporting
confidence: 92%
“…The hypothesis that a positive temporal relationship exists between the daily number of first consultations for respiratory diseases and the daily concentration of PM 10 was thus certainly confirmed in the Zagorje and Trbovlje municipalities. Moreover, these results are consistent with the results of many similar studies (23,(48)(49)(50) that also confirmed the positive association between respiratory diseases and PM 10 concentration.…”
Section: Discussionsupporting
confidence: 92%
“…Ozone can diffuse freely into cells and lead to sulfhydryl oxidation and inflammation (Frischer et al, 2001). An increased risk of asthma exacerbation associated with O 3 at levels ranging from 24.3 ppb to 60.0 ppb has been reported in previous studies (Jalaludin et al, 2008;Strickland et al, 2010).…”
Section: Discussionsupporting
confidence: 51%
“…Epidemiologic studies on school-age children have shown that exposure to ambient air pollutants were associated with increases in emergency department visits (Norris et al, 1999;Babin et al, 2007;Jalaludin et al, 2008;Strickland et al, 2010;Li et al, 2011) and hospital admissions for asthma (Lin et al, 2002(Lin et al, , 2003Tsai et al, 2006;Yang et al, 2007;Bell et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Large pediatric studies demonstrate increased asthma ED visits for increases in PM [68] and that PM 10 increases of 6.5 μg/m 3 are associated with a 15% (95% CI, 2-30%) increase in respiratoryrelated hospital admissions [69] (Table 3).…”
Section: Pm and Respiratory-related Healthcare Utilizationmentioning
confidence: 99%